Biocultural diversity linked to maize landraces of Puebla state, Mexico - Pérez-García, Oscar (Ecosistemas y Recursos Agropecuarios, 2023)
Although the theoretical- methodological advance in biocultural approaches to conservation, the reductionist vision about the biological and cultural diversity studies prevails. Maize, iconic biocultural heritage of Mexico, is an emblematic case of this problem. In this regard, I analyzed the diversity of maize landraces through biocultural approach based on a suitable database. The research was carried out in Puebla, Mexico, an important center of early Mesoamerican agriculture and maize domestication. I implemented a data mining analysis in which two database was joined together, that of indigenous maize from the CONABIO 2017 and that of native languages spoken in Mexico from the INPI 2008. This procedure was implemented to assess the richness and composition of native maize landraces under management by indigenous communities and peasant (region without indigenous communities). In contrast with the peasant communities, the number of maize landraces was significantly higher and different in indigenous communities. Moreover, indigenous communities present higher probabilities to find more maize landraces than peasant communities. Although the relevance of indigenous communities regarding the management of maize landraces, peasant communities complement and enrich this emblematic biocultural heritage.
Keywords: agrobiodiversity; data mining; indigenous communities; landrace diversity; peasants